2006
DOI: 10.1143/jjap.45.597
|View full text |Cite
|
Sign up to set email alerts
|

Bent-Core Liquid Crystals: Their Mysterious and Attractive World

Abstract: Structures and properties of liquid crystalline phases formed by bent-core molecules are reviewed. At least eight phases designated as B1-B8 have been found, being unambiguously distinguished from phases formed by usual calamitic molecules due to a number of remarkable peculiarities. In addition to B1-B8 phases, smectic A-like phases and biaxial nematic phases formed by bent-core molecules are also reviewed. The most attractive aspects of this new class of liquid crystals are in polarity and chirality, despite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
530
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 793 publications
(543 citation statements)
references
References 213 publications
5
530
0
2
Order By: Relevance
“…Especially, the location of the CoH is unknown before the motion of any tracking point (TP) is analyzed. Boomerang particles are also an interesting model system for active microswimmers [37], the electro-optical properties of DNA molecules [39][40][41][42] and the liquid crystal ordering [43].Our experimental and theoretical studies show that the diffusion of the boomerangs is rather different from that of spheres and ellipsoids. (1) The mean displacements (MD) for fixed initial angle are biased towards the CoH, and the mean square displacements (MSDs) exhibit a crossover from short to long time diffusion with different diffusion coefficients.…”
mentioning
confidence: 90%
“…Especially, the location of the CoH is unknown before the motion of any tracking point (TP) is analyzed. Boomerang particles are also an interesting model system for active microswimmers [37], the electro-optical properties of DNA molecules [39][40][41][42] and the liquid crystal ordering [43].Our experimental and theoretical studies show that the diffusion of the boomerangs is rather different from that of spheres and ellipsoids. (1) The mean displacements (MD) for fixed initial angle are biased towards the CoH, and the mean square displacements (MSDs) exhibit a crossover from short to long time diffusion with different diffusion coefficients.…”
mentioning
confidence: 90%
“…T he study of bent-core liquid crystals revealed many interesting and unique phenomena, including the interplay among chirality, molecular bend and director tilt 1 leading to peculiar layered structures labelled originally as B s (s ¼ 1-7) [2][3][4] . Remarkably, the B7 and B4 structures are helical in the micrometre 5 or nanometre 6 ranges, respectively.…”
mentioning
confidence: 99%
“…The bent-core mesogens are the first ferroelectric and antiferroelectric liquid crystals realized without introducing chirality [4]. Molecule spontaneous polarization will be incurred because of the bent molecule polarity accumulation occurred in smectic phase layer [5].…”
Section: Introductionmentioning
confidence: 99%